PENGEMBANGAN BAHAN AJAR BERBASIS ETNOSAINS PADA PEMBELAJARAN IPAS MATERI GAYA DISEKITAR KITA UNTUK SISWA KELAS IV SDN 31 CAKRANEGARA - Saskia, Ainur; Nurhasanah; Wira Zain Amrullah, Lalu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce a product in the form of ethnoscience-based teaching materials in science learning on the material of forces around us for fourth grade students of SDN 31 Cakranegara that is valid, practical, and feasible. This type of research uses the type of development research (R&D) with the Hannafin and Peck research model, which includes three main stages, namely student needs analysis, design, and development and implementation. This research was conducted at SDN 31 Cakranegara, Sandubaya sub-district, Mataram city, West Nusa Tenggara. The subjects of this study were 25 fourth grade students. The object of this study was ethnoscience-based teaching materials on the subject of science on the material of forces around us. The data collection instruments used in this study were material validation questionnaire sheets, media validation questionnaires, teacher response questionnaires, and student response questionnaires. The results of this study indicate that ethnoscience-based teaching materials obtained a percentage value of 93.63% with a very valid category by material experts and obtained a percentage value of 96.47% with a very valid category by media experts. In the practicality test by the teacher, the percentage value obtained was 96.92% with a very practical category and the practicality test by the students obtained a percentage value of 99.50% with a very practical category. Thus, it can be concluded that the overall total obtained a percentage value of 96.20% with a very feasible category. Therefore, based on the results of the study, this ethnoscience-based teaching material is very valid, practical, and feasible to be used in the science learning process of the material on the forces around us in class IV of SDN 31 Cakranegara.